FUNCTIONAL ANATOMY OF THE CENTRAL NERVOUS SYSTEM, THE SPINAL CORD AND SPINAL CORD MEMBRANES, ITS AGE-RELATED CHARACTERISTICS - Mukhammadieva Gulshakhnoza; Rustamova Odina (Modern American Journals, 2025)
The CNS integrates sensory information and coordinates motor responses. It emphasizes the functional anatomy of the spinal cord and its membranes in terms of the structural organization and their functions to provide protection. In addition, it discusses how the spinal cord and its coverings undergo age-related changes, with a focus on the implications for neurological health and function. These anatomical and physiological changes form the basis for the diagnosis and treatment of a variety of age-associated neurodegenerative diseases.
Keywords: Ventral nervous system, spinal cord, meninges, spinal cord membranes, age-related changes, neuroanatomy, neurological aging.